Effectiveness of Wire Traps and Fumigation in Controlling Rice Rats (Rattus argentiventer) in the Second Rice Planting Season - Sudarto S, Andi; Ayuningtyas Harini, Nyang Vania (Sam Ratulangi University, 2026)
The rice field rat (Rattus argentiventer) is one of the major pests in rice cultivation that can cause significant yield losses. Effective and environmentally friendly control methods are therefore essential to minimize damage. This study aims to determine the effect of using wire traps on the population of rice field rats in agricultural areas. The research was conducted by installing wire traps at several points in rice fields and comparing the number of rats caught and population changes with areas without traps. The results showed that the use of wire traps significantly reduced the population of rice field rats compared to the control area. In addition, wire traps were found to be effective, easy to use, and environmentally safe. Based on these findings, wire traps can be recommended as one of the control methods in an integrated pest management (IPM) system for rice farming. Keywords: pest control, rice, rice field rat, wire trap. Abstrak. Tikus sawah (Rattus argentiventer) merupakan salah satu hama utama pada budidaya padi yang dapat menyebabkan penurunan hasil panen secara signifikan, sehingga diperlukan metode pengendalian yang efektif dan ramah lingkungan untuk meminimalkan kerusakan. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan perangkap kawat terhadap populasi tikus sawah di area pertanian, dengan cara memasang perangkap kawat di beberapa titik di sawah lalu membandingkan jumlah tikus yang tertangkap serta perubahan populasinya dengan area tanpa perangkap. Hasil penelitian menunjukkan bahwa penggunaan perangkap kawat mampu menurunkan populasi tikus sawah secara signifikan dibandingkan dengan area kontrol, serta terbukti efektif, mudah digunakan, dan aman bagi lingkungan. Oleh karena itu, perangkap kawat dapat direkomendasikan sebagai salah satu metode pengendalian dalam sistem Pengendalian Hama Terpadu (PHT) pada budidaya padi. Kata kunci: padi, pengendalian hama, perangkap kawat, tikus sawah